A lawyer's perspective: Ethical, technical, and practical considerations in the use of linguistic expert witnesses - Ainsworth, Janet (International Journal of Speech, Language and the Law, 2010)
Linguists engaged by attorneys sometimes find their experiences as consultants and witnesses confusing and frustrating. To some extent, this may be an inevitable consequence of the adversarial justice system, but it also can reflect linguists’ misunderstanding of the obligations imposed by the ethical rules governing the practice of law. These rules can engender a skeptical assessment of the linguist’s expertise and analysis by the lawyers in the case—the hiring lawyer no less than opposing counsel. Discovery rules can create traps for the unwary expert that can undermine the expert’s credibility in this case and in cases in the future. While the hiring lawyer can properly explore the limits of what the expert can provide as helpful testimony, the linguist must resist the seductive lure of becoming a “hired gun.”